Contract academic staff career development: An oxymoron? - Bennet, Laura; Nicholson, Louise; Gunn, Alistair (New Zealand Science Review, 2005)
​As part of its Strategic Review, the New Zealand Tertiary Education Commission (TEC) is seeking to foster a broad discussion about the issues confronting the research workforce. This paper examines the increasing predominance of contract or ‘temporary’ staff amongst research academics in biomedical sciences. This transformation of the academic workforce has gone almost unnoticed amongst the wider community. However, New Zealand’s research performance is critical to developing the knowledge-based economy. As highlighted in major reviews overseas, the instability associated with an excessive dependence on contract staff for research has major implications for the future. We explore some of the factors behind this transformation, implications for research and academic performance, and some potential policy changes that have been proposed to mitigate its effects. This review particularly highlights an immediate policy issue, in that we found that there are no systematic data to either quantify the changes over time or the current extent of New Zealand’s dependence on contract staff for tertiary research and teaching.